Difficult-to-treat pathogens significantly reduce infection resolution in periprosthetic joint infections - Wimmer, Matthias Dominik; Hischebeth, Gunnar T. R.; Randau, Thomas M.; Gathen, Martin; Schildberg, Frank A.; Fröschen, Frank S.; Kohlhof, Hendrik; Gravius, Sascha (Diagnostic microbiology and infectious disease, 2020)
Periprosthetic joint infection (PJI) is a feared complication after arthroplasty. Our hypothesis was that PJI caused by difficult-to-treat (DTT) pathogens has a worse outcome compared with non-DTT PJI. Routine clinical data on 77 consecutive patients with confirmed PJI treated with 2-stage exchange arthroplasty were placed in DTT and non-DTT PJI groups and analyzed. The main outcome variable was that the patient was definitively free of infection after 2 years. We found definitive infection resolution in 31 patients in the DTT group (68.9%) and 28 patients (87.5%) in the non-DTT group (P < 0.05). The necessity for revision surgery until assumed resolution of infection was significantly more frequent in the DTT group with 4.72 ± 3.03 operations versus 2.41 ± 3.02 operations in the non-DTT group (P < 0.05). PJI caused by DTT bacteria is associated with significantly higher numbers of revision operations and significantly inferior definitive infection resolution.
Online verfügbar: 20. Juni 2020
Gesehen am 07.08.2025